2015
DOI: 10.1302/0301-620x.97b2.34057
|View full text |Cite
|
Sign up to set email alerts
|

Social deprivation as a risk factor for fractures in childhood

Abstract: Paediatric fractures are common and can cause significant morbidity. Socioeconomic deprivation is associated with an increased incidence of fractures in both adults and children, but little is known about the epidemiology of paediatric fractures. In this study we investigated the effect of social deprivation on the epidemiology of paediatric fractures. We compiled a prospective database of all fractures in children aged < 16 years presenting to the study centre. Demographics, type of fracture, mode of injury a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…Within orthopaedic surgery, numerous studies have analyzed the relationship between socioeconomic deprivation and fracture incidence in adults, noting that individuals from more deprived regions are at a higher risk for fracture 16 - 20 . There is a similar relationship between social deprivation and fracture risk in adolescents, including the humerus, the distal part of the radius, or hand fractures 21 - 23 .…”
mentioning
confidence: 89%
“…Within orthopaedic surgery, numerous studies have analyzed the relationship between socioeconomic deprivation and fracture incidence in adults, noting that individuals from more deprived regions are at a higher risk for fracture 16 - 20 . There is a similar relationship between social deprivation and fracture risk in adolescents, including the humerus, the distal part of the radius, or hand fractures 21 - 23 .…”
mentioning
confidence: 89%
“…[2] Furthermore, there is evidence from some, but not all studies,[3] to suggest that sustaining a fracture in childhood is associated with lower indices of bone strength[4] and an increased risk of fracture in adulthood. [5] Previous studies have found considerable variation in incidence rates of childhood fracture across European countries, ranging from 120 to 361 per 10,000 person years (Table 1) [1, 6-17], although recent epidemiological studies from Scandinavia have suggested that overall childhood fracture incidence increased from the mid to late 20 th century and has been followed by a more recent plateau or decline. [6, 8, 15] It is well recognised that childhood fractures are more common in boys than girls [12], and peak in incidence during the puberty [12], however, there are few published data pertaining to geographic or ethnic variation in fracture rates within a single country.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In our study, we described fracture distribution, mechanism of injuries and their differences in distinct age groups and gender among the paediatric population. The observation suggested that there was an overall predominance of males over females with the ratio of 2:1 and was highest among the school going children.…”
Section: Discussionmentioning
confidence: 98%